Changes in serum lipid profiles caused by three regimens of interferon‐free direct‐acting antivirals for patients infected with hepatitis C virus. Issue 3 (22nd September 2017) - Inoue, Takako; Goto, Takaaki; Iio, Etsuko; Matsunami, Kayoko; Fujiwara, Kei; Shinkai, Noboru; Matsuura, Kentaro; Matsui, Takeshi; Nojiri, Shunsuke; Tanaka, Yasuhito
Abstract : Aim: Serum low‐density lipoprotein cholesterol (LDL‐C) increases during treatment of chronic hepatitis C (CHC) with interferon‐free direct‐acting antivirals (DAAs). We sought to compare the changes of serum lipid profiles caused by three regimens. Methods: A total of 216 CHC patients were enrolled. Among 170 patients infected with hepatitis C virus (HCV) genotype 1b, 85 received daclatasvir plus asunaprevir (DCV/ASV) and 85 received sofosbuvir plus ledipasvir (SOF/LDV). Forty‐six infected with HCV genotype 2 received sofosbuvir plus ribavirin (SOF/RBV). Serum total cholesterol (TC), LDL‐C, high‐density lipoprotein cholesterol, and triglyceride were measured at baseline and 4, 8, 12 (for all regimens), and 24 weeks (for DCV/ASV) during treatment (4w, 8w, 12w, and 24w, respectively) and 12 and 24 weeks after treatment (p12w and p24w, respectively). Results: In 69 (81.2%) patients who received DCV/ASV and achieved a sustained virologic response at 24 weeks after the end of treatment (SVR24), TC and LDL‐C increased significantly from baseline to p24w. In 84 (98.8%) treated with SOF/LDV who achieved SVR24, TC and LDL‐C increased significantly from baseline to 8w, and TC decreased significantly from 8w to p12w. The 45 (97.8%) who received SOF/RBV and achieved SVR24 showed no significant changes. At 12w, TC and LDL‐C increased to a greater degree in patients receiving SOF/LDV than in those receiving DCV/ASV or SOF/RBV. Conclusion: During treatment with DAAs, the serum lipid profile may reflect not only recovery from the disruption of lipid metabolism induced by HCV, but also the pharmacological effects of DAAs. Further investigations are needed to elucidate the effect of DAAs on serum lipid profiles.